Reading Joyce’s Ulysses - Schwarz, Daniel R. author. aut Link
XIII, 295 p.
Keywords: Reissued to commemorate the 100th anniversary of Bloomsday, Reading Joyce's 'Ulysses' includes a new preface taking account of scholarly and critical development since its original publication. It shows how the now important issues of post-colonialism, feminism, Irish Studies and urban culture are addressed within the text, as well as a discussion of how the book can be used by both beginners and seasoned readers. Schwarz not only presents a powerful and original reading of Joyce's great epic novel, but discusses it in terms of a dialogue between recent and more traditional theory. Focusing on what he calls the odyssean reader, Schwarz demonstrates how the experience of reading Ulysses involves responding both to traditional plot and character, and to the novel's stylistic experiments.